2021
DOI: 10.5194/essd-13-5191-2021
|View full text |Cite
|
Sign up to set email alerts
|

Towards a regional high-resolution bathymetry of the North West Shelf of Australia based on Sentinel-2 satellite images, 3D seismic surveys, and historical datasets

Abstract: Abstract. High-resolution bathymetry forms critical datasets for marine geoscientists. It can be used to characterize the seafloor and its marine habitats, to understand past sedimentary records, and even to support the development of offshore engineering projects. Most methods to acquire bathymetry data are costly and can only be practically deployed in relatively small areas. It is therefore critical to develop cost-effective and advanced techniques to produce regional-scale bathymetry datasets. This paper p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…during spring tides). Bathymetry displaying shallow waters (pale blue) and deeper waters reaching 20 m (darker blue; Lebrec et al 2021). line transects along the western coast of Exmouth Gulf, covering an area of approximately 150 km 2 (Fig.…”
Section: Boat-based Data Collectionmentioning
confidence: 99%
“…during spring tides). Bathymetry displaying shallow waters (pale blue) and deeper waters reaching 20 m (darker blue; Lebrec et al 2021). line transects along the western coast of Exmouth Gulf, covering an area of approximately 150 km 2 (Fig.…”
Section: Boat-based Data Collectionmentioning
confidence: 99%
“…The in-line/cross-line bin size (i.e., horizontal resolution) are respectively 20 m × 25 m, 18.75 m × 12.5 m, and 28 m × 12.5 m, with a vertical sampling rate of 3 ms (Carnarvon 3D) to 4 ms (Gorgon 3D and Minden 3D). Range of dominant frequencies (~10-50 Hz for Gorgon 3D and Minden 3D; ~20-70 Hz for Carnarvon 3D), interval velocities at the seafloor (~1500 m/s; Lebrec et al, 2021;Li and Hewett, 2016) and interval velocities in the shallow subsurface of the study area (~2000 m/s; Riera et al, 2019) indicate a vertical resolution ranging from 5 m (small beds) to 37.5 m (thicker structures) at the seafloor, and from 7 m to 50 m in the subsurface.…”
Section: Methodsmentioning
confidence: 99%
“…Monk et al (2016) identified outcropping reef features, up to 2 m in height, along the Northeast Tasmanian Shelf. The ridges were often undercut forming small caves and ledges, and extended along the shelf for distances of 100 m to 1 km scales at depths of 60–90 m. Bezore et al (2016) identified prominent relict shoreline cliffs with 14 m relief and sea stacks off Victoria's Otway coast in water depths of 60 m. In addition to these studies, a novel repurposing of petroleum exploration 3D seismic datasets, O'Leary et al, 2020 and Lebrec et al, 2021 were able to use the ‘first‐return’ seismic reflector (i.e., the seabed) to model seabed bathymetry over tens of thousands of square kilometres of continental shelf, which revealed extensive and very well preserved submerged shoreline features and associated environments.…”
Section: Sea Floor Mapping: Revealing Submerged Countrymentioning
confidence: 98%
“…Unfortunately, limitations in the spatial coverage of high-resolution bathymetry (Lebrec et al, 2021(Lebrec et al, , 2022 as well as uncertainties in the extent to which a transgressing marine shoreline could erode landforms or destroy cultural sites (Veth et al, 2020) had tended to discourage investigations into Indigenous underwater cultural heritage around the Australian margin. However, in a somewhat serendipitous outcome, while most seabed mapping efforts in Australia are primarily focused on characterising benthic habitats, they have also identified in the course of their mapping, relict shoreline features.…”
Section: Sea Floor Mapping: Revealing Submerged Countrymentioning
confidence: 99%